2016
DOI: 10.1139/cjm-2015-0725
|View full text |Cite
|
Sign up to set email alerts
|

Might dolutegravir be part of a functional cure for HIV?

Abstract: Antiretroviral therapy (ART) has greatly decreased HIV-related morbidity and mortality. However, HIV can establish viral reservoirs that evade both the immune system and ART. Dolutegravir (DTG) is a secondgeneration integrase strand transfer inhibitor (INSTI) related to the first-generation INSTIs raltegravir (RAL) and elvitegravir (EVG). DTG shows a higher genetic barrier to the development of HIV-1 resistance than RAL and EVG. More interestingly, clinical resistance mutations to DTG in treatment-naïve patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…In vitro, the most common mutation against DTG is the R263K that severely reduces viral replication fitness, reducing the impact and rendering it insignificant for HIV/AIDS treatments 48 . Prevention of renewed viral infection emerging from tissue reservoirs experiencing suboptimal drug levels may allow infected cells to die off through normal cell turnover without spreading virus to other cells that may act as viral reservoirs 49 . Thus, the changes in antiretroviral drug treatment made here could limit viral replication in its native reservoirs, allowing antiretroviral drugs alone to keep the virus in check and attenuate new infections.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the most common mutation against DTG is the R263K that severely reduces viral replication fitness, reducing the impact and rendering it insignificant for HIV/AIDS treatments 48 . Prevention of renewed viral infection emerging from tissue reservoirs experiencing suboptimal drug levels may allow infected cells to die off through normal cell turnover without spreading virus to other cells that may act as viral reservoirs 49 . Thus, the changes in antiretroviral drug treatment made here could limit viral replication in its native reservoirs, allowing antiretroviral drugs alone to keep the virus in check and attenuate new infections.…”
Section: Discussionmentioning
confidence: 99%
“…What is notable about this substitution is that, unlike those discussed for RAL and EVG, the R263K substitution only results in low levels of resistance to DTG. It also has a significant impact on the fitness of the virus, and has yet to be compensated by secondary resistance mutations in tissue culture selections [33, 83]. It has been reported that patients with non-B subtype viruses selected for N155 pathway mutations in response to DTG (Table 3; see also [35]).…”
Section: Second-generation Instismentioning
confidence: 99%
“…Several findings support that early treatment with DTG may reduce the emergence of HIV-1 drug resistance (HIVDR) in resource-limited settings (RLS) [15]. These evidences are in line with the WHO recommendations on transitioning to DTG-based regimens for initial option or alternative ART in case of multi-resistance [10,11]. Up-to-date, few African countries carried out studies on INSTI-resistance.…”
Section: Introductionmentioning
confidence: 63%
“…These INSTIs are highly effective in both treatment-naïve as well as in treatment-experienced individuals who may harbor multidrug resistance to other drug classes, with a superior efficacy of DTG, CAB, and BIC both in vitro and in vivo [2,4,7]. These latter molecules are known as second generation while RAL and EVG are first-generation INSTI [1,3,[7][8][9][10][11]. In the group of second-generation INSTI, BIC has been recently approved by the US Food and Drug Administration (FDA) and exist only as part of the fixed dose combination bictegravir/emtricitabine/tenofovir alafenamide (BIC/3TC/TAF) [12,13].…”
Section: Introductionmentioning
confidence: 99%